PROPER NOUNS IN ENGLISH AND UZBEK: LINGUISTIC CHARACTERISTICS AND TRANSLATIONAL ASPECTS - Olimova Xurshida Vaydillayevna; Feruza Mamashukurova (Innovate Conferences, 2025)
The article addresses issues such as the principles of naming and the development of the nomination process, while showing that proper nouns are directly related to the anthropocentric interpretation. Furthermore, it demonstrates that proper nouns pertain to several fields, including ethnolinguistics, linguistic aesthetics, and areal linguistics. The article also concludes that proper nouns have a complex structure consisting of both linguistic and extralinguistic components.
Keywords: syntactic sign, areal linguistics, linguoesthetics, ethnolinguistics, noun.